Molecular profiling of multi-coloured flesh potato (Solanum tuberosum) hybrids and interspecific somatic hybrids using SSR markers - KUMAR TIWARI, JAGESH; K LUHRA, SATISH; ZINTA, RASNA; BUCKSETH, TANUJA; K SINGH, RAJESH; KUMAR, MANOJ (The Indian Journal of Agricultural Sciences, 2022)
The objective of this study was to develop SSR profiles of potato (Solanum tuberosum L.) hybrids for genetic fidelity purpose. The multi-coloured flesh potato hybrids and interspecific somatic hybrids-derived progenies were for the study conducted at ICAR-CPRI, Shimla during 2019–20. A total of 165 potato genotypes were analysed using two well-known potato SSR markers (STU6SNRN and STIIKA). High polymorphism was observed in STIIKA (PIC: 0.93) than STU6SNRN (PIC: 0.82), and higher number of alleles were observed in STIIKA (23) than STU6SNRN (7). In STU6SNRN, alleles size 174, 179, 182, 190 and 200 bp were predominant whereas in STIIKA, alleles size 191, 195, 198, 201, 221, 223, 231, 242, 245 and 256 were observed frequently in more than 50% of the genotypes. Diversity analysis showed a clear distinction among the genotypes based on the Jaccard dissimilarity coefficient by the Neighbour-joining tree method using the DARwin software. SSR fingerprints would be valuable resources to strengthen genetic fidelity of these hybrids and identification of true-to-type clones.